2005
DOI: 10.1504/ijhpcn.2005.007866
|View full text |Cite
|
Sign up to set email alerts
|

Fault-tolerant cycle embedding in dual-cube with node faults

Abstract: A low-degree dual-cube was proposed as an alternative to the hypercubes. A dual-cube DC(m) has m + 1 links per node where m is the degree of a cluster (m-cube) and one more link is used for connecting to a node in another cluster. There are 2 m+1 clusters and hence the total number of nodes is 2 2m+1 in a DC(m). In this paper, by using Gray code, we show that there exists a faulty-free cycle containing at least 2 2m+1 − 2 f nodes with f ≤ m − 1 faulty nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Its nice structure has drawn the attention of many researchers [11,[15][16][17][18][19][20]. A dual-cube DC n is obtained from a basic component Q n as follows.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Its nice structure has drawn the attention of many researchers [11,[15][16][17][18][19][20]. A dual-cube DC n is obtained from a basic component Q n as follows.…”
Section: Preliminariesmentioning
confidence: 99%
“…By the definition of DC n and the study of [20], we know that DC n is an (n + 1)-regular bipartite graph. Any vertex u in DC n is adjacent to n vertices in the same cluster and to one vertex in some cluster of the other class.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, various fault-tolerant measures have been proposed in the literature, including fault diameter, fault Hamiltonicity, fault pancyclicity, fault Hamiltonian laceability, etc. The random fault model considered in [3,4,[8][9][10]12,14,16,23], assumed faults might happen anywhere in a network without any restriction. On the other hand, under the assumption each node is incident with two or more fault-free links, it was shown [1,2] a k-ary, k P 3, n-dimensional hypercube (an n-dimensional hypercube) contains a fault-free Hamiltonian cycle, even if there are up to 4n À 5 (2n À 5) link faults.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [4] showed that DC(n) contains a fault-free Hamiltonian cycle even if it has up to n − 1 edge faults for n 2. Subsequently, they showed [5] that there exists a fault-free cycle containing at least 2 2n+1 − 2 f vertices in DC(n), n 3, with f n faulty nodes.…”
Section: Introductionmentioning
confidence: 99%